Conjunctive Analyses of Bulk Segregant Analysis Sequencing and Bulk Segregant RNA Sequencing to Identify Candidate Genes Controlling Spikelet Sterility of Foxtail Millet - Gao, Yongbin; Du, Lihong; Ma, Qian; Yuan, Yuhao; Liu, Jinrong; Song, Hui; Feng, Baili (Frontiers in Plant Science, 2022)
Foxtail millet has gradually become a model gramineous C4 crop owing to its short growth period and small genome. Research on the development of its spikelets is not only directly related to the yield and economic value of foxtail millet but also can provide a reference for studying the fertility of other C4 crops. In this study, a hybrid population containing 200 offspring was constructed from the Xinong8852 and An15 parental lines, and two extreme trait populations were constructed from the F2 generation for analysis of the spikelet sterility. The F2 population conformed to a 3:1 Mendelian segregation ratio, and it was thus concluded that this trait is likely controlled by a single recessive gene. Bulk segregant analysis sequencing (BSA-Seq) was used to determine the candidate regions and candidate genes related to the development of foxtail millet spikelets. Additionally, the functional analysis of differentially expressed genes in populations with different traits was conducted by bulk segregant RNA sequencing (BSR-Seq). Finally, conjunctive analysis of BSA-Seq and BSR-Seq results, combined with biological information analysis, revealed six genes on chromosome VII that were ultimately identified as candidate genes controlling foxtail millet spikelet development. This study provides a new reference for research on foxtail millet sterility and lays a solid foundation for the examination of fertility in other gramineous crops.